Robust and sustainable Mg1-xCexNiyFe2-yO4 magnetic nanophotocatalysts with improved photocatalytic performance towards photodegradation of crystal violet and rhodamine B pollutants. (May 2022) - Jasrotia, Rohit; Prakash, Jyoti; Kumar, Gagan; Verma, Ritesh; Kumari, Swati; Kumar, Sachin; Singh, Virender Pratap; Nadda, Ashok K.; Kalia, Susheel
Abstract: This study aims at manufacturing Ce 3+ /Ni 2+ ions doped Mg nanoferrites by the sol-gel method for the photocatalytic degradation of rhodamine B and crystal violet pollutants under visible natural sunlight. The particle size of synthesized nanoferrites was calculated through XRD, Hall-William plots, and TEM analysis, which perfectly agree with each other. FTIR study investigated the existence of stretching vibrations in M − O (metal-oxygen) complexes at the tetrahedral (A-site) and octahedral sites (B-site). The Raman spectra of synthesized nanophotocatalysts show the presence of four vibrational modes (Eg + 2T2g + A1g ), providing suitable information of occupancy of Mg 2+, Ce 3+, Ni 2+, and Fe 3+ ions at the interstitial sites of undoped and Ce 3+ /Ni 2+ doped MgFe2 O4 crystal structure. The synthesized MGF3 nanophotocatalyst performs well with degradation of 97.674% crystal violet (CV) and 90.05% rhodamine B (RhB) under natural sunlight in 60 min. The experimental results showed that doped MgFe2 O4 nanoferrites have a high tendency to photodegrade the RhB and CV dyes in an aqueous form. The pseudo-first-order equation reflects the best photocatalytic process kinetics and studied the feasibility of RhB and CV dyes adsorption on the doped and undoped MgFe2 O4 nanoferrites. The results show good support for adsorption by the spontaneous photodegradation process. The excellent photocatalytic activity of synthesized nanoferrites under natural sunlight verifies them as a potential candidate for the photodegradation of organic dyes. Finally, the antibacterial activity of magnetic nanoferrites was examined against S. aureus and E. Coli. The studies demonstrated that synthesized magnetic nanoferrites were more effective against S. aureus . Highlights: Synthesis of Ce 3+ /Ni 2+ ions doped nanoferrites by the Sol-gel auto-combustion method. Pristine and doped MgFe2 O4 nanoferrites exhibit spinel cubic structure. Doped MgFe2 O4 nanoferrites proved their better photocatalytic performance. Magnetic nanoferrites exhibit antibacterial activity against S. aureus and E. coli .